Perencanaan Pembelajaran Bahasa Arab Abad 21 di Madrasah : Perspektif Filosofis, Sosiologis, dan Psikologis - Sumarni; Een Mu'arofah; Nina Agustina Komariah; Miskah; Anisa Rihadatul A’isy; Mochamad Mu'izzuddin; Zaki Ghufron (Prodi Pendidikan Bahasa Arab FTK UIN Sunan Ampel, 2026)
Purpose - This study aims to identify and analyze the direction of Arabic learning planning that is relevant to the demands of the 21st century in madrasas. The main focus of this study is to review the planning from the three main foundations of education, namely philosophical, sociological, and psychological foundations, in order to provide a conceptual reference for education in designing contextual and effective learning. Design/Methodology/Approach - This research uses a qualitative approach with the library research method. Primary data is sourced from the Arabic language learning policy document in madrassas (KMA Number of 2022), while secondary data includes related academic literature from the last ten years. The data analysis technique used is content analysis through the stages of identification, selection, classification, and comparative interpretation of themes. Findings - The results of the study conclude that 21st-century Arabic language learning planning must integrate philosophical foundations (focus on critical thinking skills and character), sociological foundations (formation of socio-religious identity and global responsiveness), and psychological foundations (adaptation to students' learning styles and motivations). This integrity results in the learning model of communicative, contextual, humanist and adaptive learning models, which are not only oriented towards mastering language structures but also on practical communication competencies. Research Limitation/Implications - This study is limited to a literature review and therefore has not tested the implementation of the conceptual model in the field. Nevertheless, the findings offer conceptual contributions and practical implications that can serve as a reference for teachers and curriculum developers in designing more comprehensive 21st-century Arabic language lesson plans that are relevant to the needs of modern education.